EFQM Model and Agility of Organizations (Journal of Universal Excellence, 2026)
Research question (RV): What is the contribution of an organization that follows the EFQM model and reorganizes its organization into an agile organization?Purpose: The purpose of the research is to examine the interrelationship between the EFQM model, agility and agile organization, and consequently faster adaptability, greater performance and competitiveness of the agile organization.Method: The article was based on a review of foreign and domestic literature. We reviewed the professional literature on agility and the EFQM model. We searched a link between agility and the EFQM model.Results: We will find that there are differences between agile management and organizational culture in organizations that are agile aware from those that are not. It is essential for successful agile organization leaders to develop effective communication and interaction skills that are unique to the leader and organization. It is important that individuals in the organization adopt a shared vision, participate in a culture of trust and inclusion, while leaders encourage creativity and experimentation.Organization: An agile organization is considered to be fast (innovative, agile, adaptable) and that it is necessary to constantly renew its business. The research will draw attention to the importance and necessity of management awareness that by creating a certain organizational culture and agile management of the organization, they will achieve faster and more efficient adaptation to changes in the environment.Society: The lack of agile management and the creation of an inappropriate organizational culture has a negative impact on the satisfaction of all involved in the process (employees, customers, suppliers) and consequently on adapting to the needs of the environment.Originality: The originality of the article lies in breaking down the myths about the concept of agility and agile organization, and presenting or evaluating the obtained results with the result of differences between agile and not agile or traditional organizations.Limitations / further research: The limitation represents a small number of articles and literature selected for comparison. Based on a larger sample of articles, we would get more relevant results. We also found a few articles in Slovenian.
Keywords: business excellence; EFQM model; agile management; agility; agile organization